2000
DOI: 10.1128/mcb.20.12.4428-4435.2000
|View full text |Cite|
|
Sign up to set email alerts
|

A Zinc Finger Transcription Factor, αA-Crystallin Binding Protein 1, Is a Negative Regulator of the Chondrocyte-Specific Enhancer of the α1(II) Collagen Gene

Abstract: Transcription of the type II collagen gene (Col2a1) is regulated by multiple cis-acting sites. The enhancer element, which is located in the first intron, is necessary for high-level and cartilage-specific expression of Col2a1. A mouse limb bud cDNA expression library was screened by the Saccharomyces cerevisiae one-hybrid screening method to identify protein factors bound to the enhancer. A zinc finger protein, ␣A-crystallin binding protein 1 (CRYBP1), which had been reported to bind to the mouse ␣A-crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…During hypertrophic differentiation, the extracellular matrix self-organizes prior to the formation of bone. A switch from collagen type II to collagen type X occurs, and both aggrecan and link protein disappear (1,2). Studies in stable transformants revealed that overexpression of Snail and Slug prevented the expression of major chondrocyte extracellular matrix, collagen type II, and aggrecan when transfected cells were induced to differentiate.…”
Section: Snail-related Transcription Factors Are Repressors Of the Comentioning
confidence: 99%
See 1 more Smart Citation
“…During hypertrophic differentiation, the extracellular matrix self-organizes prior to the formation of bone. A switch from collagen type II to collagen type X occurs, and both aggrecan and link protein disappear (1,2). Studies in stable transformants revealed that overexpression of Snail and Slug prevented the expression of major chondrocyte extracellular matrix, collagen type II, and aggrecan when transfected cells were induced to differentiate.…”
Section: Snail-related Transcription Factors Are Repressors Of the Comentioning
confidence: 99%
“…Type II collagen and aggrecan are major components of the cartilage extracellular matrix produced by proliferating and prehypertrophic chondrocytes, and type X collagen is a major collagen type produced by hypertrophic chondrocytes. The differentiation into hypertrophic chondrocytes is accompanied with changes in ECM; switching of collagen types from type II to type X and the disappearance of aggrecan and link protein (1,2). Dysfunction of these extracellular macromolecules in mutant mice results in striking skeletal malformation, suggesting their important roles in skeletal formation (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Members of the ZAS family have been shown to inhibit transcription. ZAS1 negatively regulates the ␣1(II) collagen gene (27), whereas ZAS2 represses c-myc transcription from the major P2 promoter (28).…”
Section: Zas3 Directly Represses Nf-b-mediatedmentioning
confidence: 99%
“…The best studied gene in this regard is the COL2A1 gene, which gives rise to the main fibrillar collagen in the cartilage matrix. The expression of the COL2A1 gene is controlled through transcription factors that interact with both the promoter and the chondrocyte-specific enhancer located within the first intron (1)(2)(3)(4). Recent work has shown that both positive and negative factors interact with the COL2A1 gene to regulate its expression (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The expression of the COL2A1 gene is controlled through transcription factors that interact with both the promoter and the chondrocyte-specific enhancer located within the first intron (1)(2)(3)(4). Recent work has shown that both positive and negative factors interact with the COL2A1 gene to regulate its expression (2)(3)(4)(5)(6)(7)(8). Positive regulation of the COL2A1 gene during chondrocyte differentiation is afforded by the interaction of members of the Sry-type HMG box (SOX) 1 family of transcription factors with a specific region of the intronic enhancer (5)(6)(7)(8).…”
mentioning
confidence: 99%